Forjado em sangue: a ancestralidade do vampiro cinematográfico - Humphreys, Juliana Porto Chacon (2014)
This research aims to examine the route of the vampire figure in film, tracing a line of ancestry that starts in early influences found in medieval art, through the transmutations within the Gothic and Romantic literature, until contemporaneously, their cinematic recreations. It is about to understand the factors that forged the figure of the vampire in current cinema, especially regarding to its status as an undead male and to the arising horror effects. Thus, the object of study assumes two distinct phases: primary, enclosed by the figure of the vampire in film; and secondary, comprising a cutout of fantastic literature. Being hybrid, the research corpus comprises, at first, a set of works of the XV century called Dance macabre, plus a small sample of tales of the XVIII and XIX centuries with vampire theme, culminating in the work Dracula, by Bram Stoker, on 1897. Secondly, but more importantly, about a century set of extensive and representative vampire filmography that includes the transformation of the vampire image, starting with Nosferatu, on 1922; and finishing with Shadows of the Night, on 2011. The assumptions that guide the study deal with the relationship between the attraction exerted by the vampires and their increasing aestheticization; detachment between cinematic vampires and the literary array of Bram Stoker's Dracula and the consequent spread of reconfigurations of character retrieve the medieval influences. Forcibly multidisciplinary, the theoretical references of research include studies in Art History, History of Literature and the History of Cinema, as an instrument of semiotic analysis, which in this case will be Greimas for literature and Peirce for images. Supported by this background, the study also aims to contribute significantly to the study of the figure of the vampire, highlighting the influences that determined the existence of one of the most important horror characters of the first century of cinema